The development of methods of analysis of balance sheet liquidity and company’s solvency - S. A. Sidorova (Путеводитель предпринимателя)
In the article there is a research of the industry average indexes of balance sheet liquidity and company’s solvency of the industry «Stone mining for monuments and construction», which is an analytical basis.